PENGEMBANGAN PERANGKAT EKSPERIMEN OERSTED SEBAGAI MEDIA PEMBELAJARAN FISIKA - Ridho, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The aim of this research is to produce an Oersted experimental device to support laerning prosess of junior and also senior high schools. In this development research method, we have developed Oersted experimental device and its guide through the step of ADDIE method. Three leacturs of physics education and two physics teachers were participant is expert and user repectly. They asked to asses the construction and content validity of the device. Base on the data analyzed, we found that Oersted exprimental device is valid. So, according to experts and users adjudge, we concluded that Oersted experimental device can be used as physics learning media on magnetic field of induction current.Key word: Magnetic Field of Induction, Oersted Experimental Device, Validity.